Effectiveness of smart health-based rehabilitation on patients with poststroke dysphagia: A brief research report - Zhang, Jian-Rong; Wu, Yu-E; Huang, Yan-Fang; Zhang, Shu-Qing; Pan, Wen-Li; Huang, Jin-Xia; Huang, Qing-Ping (Frontiers in Neurology, 2023)
Objective. This study aimed to evaluate the effectiveness of smart health-based rehabilitation on patients with PSD.Methods. We recruited 60 PSD patients and randomly allocated them to the intervention (n=30) and control (n=30) groups. The former received the smart health-based rehabilitation for 12 weeks, whereas the latter received routine rehabilitation.WST, standardised SSA, SWAL-QOL, SSEQ,PSSS and nutritional measurements including body weight, TSF, TP, ALB and PA in both groups were measured.Results. When the baseline WST, SSA, SWAL-QOL, SSEQ, PSSS and nutritional measurements were examined, there was no significant difference between the intervention group and the control group (P>0.05). After rehabilitation interventions, the WST and SSA scores in the intervention group were significantly lower than those in the control group (P<0.01). The SWAL-QOL, SSEQ and PSSS scores in the intervention group were significantly higher than in the control group (P<0.01). Compared with the control group, the intervention group showed an increase in the serum levels of PA (P<0.01).Conclusions. Overall, our data revealed that smart health-based rehabilitation is significantly beneficial to the swallowing function, quality of life, self-efficacy, and social support for PSD patients when compared with routine rehabilitation. However, nutritional measurements were not significantly improved in such patients under the smart health-based rehabilitation when compared the routine rehabilitation. In the future, it is necessary to extend the intervention time to further evaluate the long-term efficacy of smart health-based rehabilitation on nutritional measurements of PSD patients.